PERAN KEARIFAN LOKAL DALAM PEMBENTUKAN IDENTITAS PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR: KAJIAN LITERATUR ANTROPOLOGI DAN SOSIOLOGI - Iis Maesaro; Nursyamsiah, Siti; Hidayat, Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Multicultural education in Indonesia plays a strategic role in fostering a national character that values cultural diversity. This study aims to explore the role of local wisdom in shaping the identity of multicultural education through a literature review based on sociological and anthropological perspectives in education. The research method used is a qualitative literature review, analyzing various academic sources, including journals, books, and relevant documents.The findings indicate that local wisdom, which encompasses values such as tolerance, mutual cooperation (gotong royong), and respect for differences, serves as an effective medium for building cultural identity and character among students elementary school. From a sociological perspective, multicultural education rooted in local wisdom strengthens social relationships and harmony among cultural groups. Meanwhile, from the perspective of educational anthropology, local wisdom acts as a medium for preserving traditions that enrich cross-cultural learning. However, the implementation of multicultural education based on local wisdom faces several challenges, including limited teacher understanding of local cultures, inadequate culturally relevant teaching materials, and insufficient support from national education policies. This study is expected to contribute significantly to the development of multicultural education in Indonesia and encourage more inclusive policies rooted in local culture.